Teknik Storytelling Bagi Pemuda dalam Mempromosikan Wisata di Bengkulu - Adhrianti, Lisa; Aditia, Rafinita (Abdimas Mandalika, 2026)
Abstract: This community service program aims to increase the capacity of Bengkulu youth in promoting regional tourism through storytelling techniques as a digital-based creative communication strategy. This program is implemented with a participatory and applicative approach through three main stages, namely pre-activities, core activities (training and workshops on storytelling and tourism content production), and monitoring and evaluation. The target audience is the Bujang Gadis Bengkulu community of 50 people (25 men and 25 women) who were selected because of their strategic role as tourism ambassadors and social media-based promotion agents. The results of the implementation show three main achievements. First, more than 80% of participants experienced an increase in conceptual understanding regarding the importance of storytelling in digital tourism promotion. Second, participants demonstrated increased practical skills in composing and delivering tourism narratives in a more emotional, persuasive, and audience-oriented manner. Third, participants were able to implement these techniques through promotional content on social media that encourages increased audience interaction. This program emphasizes that storytelling is a youth empowerment instrument that has the potential to support the creative and sustainable development of Bengkulu tourism.Abstrak: Pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kapasitas pemuda Bengkulu dalam mempromosikan wisata daerah melalui teknik storytelling sebagai strategi komunikasi kreatif berbasis digital. Program ini dilaksanakan dengan pendekatan partisipatif dan aplikatif melalui tiga tahapan utama, yaitu pra-kegiatan, kegiatan inti (pelatihan dan workshop storytelling serta produksi konten wisata), serta monitoring dan evaluasi. Khalayak sasaran adalah komunitas Bujang Gadis Bengkulu sebanyak 50 orang (25 laki-laki dan 25 perempuan) yang dipilih karena perannya strategis sebagai duta wisata dan agen promosi berbasis media sosial. Hasil pelaksanaan menunjukkan tiga capaian utama. Pertama, lebih dari 80% peserta mengalami peningkatan pemahaman konseptual mengenai pentingnya storytelling dalam promosi wisata digital. Kedua, peserta menunjukkan peningkatan keterampilan praktis dalam menyusun dan menyampaikan narasi wisata secara lebih emosional, persuasif, dan berorientasi pada pengalaman audiens. Ketiga, peserta mampu mengimplementasikan teknik tersebut melalui konten promosi di media sosial yang mendorong peningkatan interaksi audiens. Program ini menegaskan bahwa storytelling merupakan instrumen pemberdayaan pemuda yang berpotensi mendukung pengembangan pariwisata Bengkulu secara kreatif dan berkelanjutan.